2010
DOI: 10.1021/bc9005656
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Tumor-Targeting Drug Delivery System. Validation of Efficient Vitamin Receptor-Mediated Endocytosis and Drug Release

Abstract: An efficient mechanism-based tumor-targeting drug delivery system, based on tumor-specific vitamin-receptor mediated endocytosis, has been developed. The tumor-targeting drug delivery system is a conjugate of a tumor-targeting molecule (biotin: vitamin H or vitamin B-7), a mechanism-based self-immolative linker and a second-generation taxoid (SB-T-1214) as the cytotoxic agent. This conjugate (1) is designed to be (i) specific to the vitamin receptors overexpressed on tumor cell surface, (ii) internalized effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
282
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(287 citation statements)
references
References 44 publications
1
282
1
3
Order By: Relevance
“…46 Hcy-Mito and Hcy-Biot had the same reaction mechanisms except the targeting functions. The proposed reaction mechanism was illustrated in Scheme 1.…”
Section: Design Strategies For Probes Hcy-mito and Hcy-biotmentioning
confidence: 98%
“…46 Hcy-Mito and Hcy-Biot had the same reaction mechanisms except the targeting functions. The proposed reaction mechanism was illustrated in Scheme 1.…”
Section: Design Strategies For Probes Hcy-mito and Hcy-biotmentioning
confidence: 98%
“…Ojima et al used biotin as a tumor targeting ligand in the design of theranostic agents utilizing different anticancer drugs and fluorophores. [196][197][198] The biotinylated fluorescein coupled with SB-T-1214 via the selfimmolative disulfide linker formed theranostic agent 59.…”
Section: Thiol-mediated Modesmentioning
confidence: 99%
“…118 A study demonstrated that modification of drug delivery with biotin is an effective pattern to enhance cell specificity against the cancer cells overexpressed with biotin receptors on the cell surfaces and to accelerate the internalization of the drug delivery into the targeted cancer cells through receptor-mediated endocytosis. 119 To verify the potential value of biotin for targeted liver neoplasms, Mishra and Jain 120 designed biotinmodified erythrocytes loaded with MTX by combining with N-hydroxysuccinimide ester of biotin. In vivo study showed that the MTX level of liver administrated with biotinylated erythrocytes was increased ~3-fold compared with free MTX and 1.8-fold compared with nonbiotinylated erythrocytes at 1 h after injection into rats, indicating that this drug system could be used to place hepatic arterial catheters for locoregional treatment of liver neoplasms.…”
mentioning
confidence: 99%